Fighting the Silence - Velzen, Ilse van; Velzen, Femke van (IFProductions, 2007)
Verzio FF Submission The Democratic Republic of the Congo’s seven-year war was the deadliest ever recorded in Africa. During that time, more than 80,000 women and girls were raped. Only now that the country is formally at peace are the consequences of the brutality becoming truly visible. Rape is slowly seeping into everyday life. “Fighting the Silence” tells the story of ordinary Congolese women and men who are struggling to change their society: one that prefers to blame victims rather than prosecute rapists. Girls and women who have survived tell of the brutality they experienced. Married couples openly talk about the pain they endure. Husbands talk of the pressures that led them to abandon their wives and why they agreed to take them back. A father explains why he has given up on his daughter’s future and how he wishes he could afford to take her rapist to court. Soldiers and policemen share their (shocking) views about why rape continues to flourish despite the war having officially ended four years ago.